Retention Basin for Flood Mitigation (Case Study: Magetan Regency) - Handayani, Marita Putri; Hadiani, Rr. Rintis; Solichin, Solichin (Indonesian Journal Publisher, 2024)
Flooding is a natural event that often occurs in Indonesia. Magetan Regency has several areas drained by various rivers that have the potential to cause flooding problems in the event of high rainfall. Hydrological analysis is needed to determine the various rivers that are potentially unable to accommodate water capacity due to high rainfall, causing flooding problems. Thus, research aims to assess flood mitigation control based on a 25-year return period flood discharge (Q25) using the HSS Snyder method and HEC-HMS software. The flood inundation area due to river runoff is analysed using HEC-RAS 6.4.1 software using a 25-year return period discharge (Q25). This research uses retention basin as one of the efforts in flood mitigation, reducing the amount of flood inundation that occurs by using embankment planning. Retention basin is a water structure that functions to collect rainwater and water runoff to reduce flooding. Retention basin is one of the important steps in the flood inundation that occurred in Magetan Regency using HEC-RAS 6.4.1 software analysis was 3,75 km2. The largest flood inundation occurred in Kartoharjo District with an area 1,31 km2. The design of the Kartoharjo Retention Basin in Magetan Regency can reduce the flood inundation area by 22% to 2,94 km2.